Single-molecule imaging reveals molecular coupling between transcription and DNA repair machinery in live cells - Han Ngoc Ho (Nature Portfolio, 2020)
Mfd recognizes stalled transcriptional complexes at sites of lesions and recruits the nucleotide excision repair proteins (UvrAB) to the site. Here the authors use live cell imaging in E. coli to demonstrate that coordinated ATP hydrolysis by UvrA and loading of UvrB on DNA facilitate the dissociation of Mfd from the handoff complex.